Implementasi Media Tangram Polypad Berbasis Discovery Learning Upaya Peningkatan Hasil Belajar Materi Bangun Datar Kelas II - Utomo, Muhammad Ilham Cahyo; Purwati, Panca Dewi (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
This research was motivated by the low learning outcomes of students in mathematics subjects, especially composition and decomposition of flat shapes. The aim of this research is to describe the application of the Discovery Learning model assisted by polypad media at SD 3 Sidorejo in learning Composition and decomposition of flat shapes. the natural condition of the object, based on the philosophy of postpositivism, where the researcher is the main data collection tool. After implementing the Discovery Learning model assisted by Polypad Media on students, it can be seen from the posttest results in the table that learning using the Discovery Learning model assisted by Polypad Media can improve student learning outcomes. This supports students to better understand the material provided by the teacher. So learning will be fun and the material will be easier to understand because it is student-centered and carried out with many activities.